The Speaking that Silence Is: Prayer as Openness to God. (December 2013) - Nelson, Derek R.
Abstract Prayer exists as the dialectic between speaking and falling silent that presupposes, assumes and furthers the openness of the whole self to God. Prayer as speaking comprises thanksgiving, confession, petition, and instruction. Instruction includes a Torah‐like understanding of God's word as law, following Martin Luther. Prayer as silence includes the silence of confusion, the silence of expectation, and the silence of submission, following Søren Kierkegaard.